Remedies, Enforcement and Territoriality - Mazziotti, Giuseppe (The Columbia Journal of Law & the Arts, 2018)
I would like to start by thanking the Kernochan Center and all its members, in particular Jane Ginsburg, and also Rebecca Giblin, together with all the colleagues who have been involved in the conception of this Symposium. I am happy to be back after a few years: I was a Visiting Scholar at Columbia Law School in the academic year 2011 and I was very lucky to be invited to speak at the 2011 annual copyright symposium on collective rights management. I am happy to talk briefly about the implications of territoriality for online copyright enforcement measures. As it has been remarked earlier today, territoriality is a principle established indirectly in many ways by the Berne Convention.1 Territoriality also plays a central role for a number of copyright enforcement measures that have become extremely important for the creative sector in the digital environment.